M ssing [videorecording (DVD)] - Costa-Gavras, 1933-; Lemmon, Jack; Spacek, Sissy; Shea, John, 1949-; Hauser, Thomas (Criterion collection, 2008)
Dramatizes the search for American journalist Charles Horman who disappeared during the 1973 military coup in Chile.